HLA-DR3 and DQA1*0401: possible risk factors in Alzheimer's disease - Culpan, D; MacGowan, S; Laundy, G; Wilcock, G (1999)
It has been suggested that an immune response may contribute to the pathogenesis of Alzheimer's disease (AD), and therefore several studies have examined the possible association of AD with the Major Histocompatibility Complex (HLA). In order to investigate whether there is susceptibility to AD involving the HLA class II antigens, we studied 97 AD patients and 53 controls. Our study included the HLA-class II subgroups DRB1, DQA1 and DQB1. We also investigated whether there is a significant association between different HLA-class II alleles and the apolipoprotein E ε4 allele (apoE ε4), an established genetic risk factor for AD. Univariate analysis established an association between the apoE ε4 allele and AD, as expected. When HLA-DRB1, DQA1 and DQB1 were analysed as independent genes, we found an association between the presence of DQA1*0401 and AD. However this may be because of the small numbers in our AD population and the total absence of the allele in our control population. Using logistic regression analysis including apoE genotype, HLA-DRB1, DQB1 and DQA1 alleles as potential predictors of the presence of AD, only apoE ε4 status and the absence of the DR3 allele showed a significant association with AD. This further weakens the possible association of AD and DQA1*0401. There was no association with either HLA-DR3 or DQA1*0401 and the apoE genotype. © MSJ Alzheimer's disease Apolipoprotein E HLA.